2021
DOI: 10.1007/s10198-021-01384-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the cost-effective threshold of a quality-adjusted life year in China based on the value of statistical life

Abstract: Cost-effective threshold (CET) is essential for health technology assessment and decision-making based on health economic evaluations. Recently, it has been argued that the commonly used once and three times of gross domestic product (GDP) per capita CETs of a quality-adjusted life year (QALY) are not necessarily empirically supported in all countries. Therefore, we aimed to estimate the CET of a QALY as times of GDP per capita in China, of which the reimbursement coverage decisions are increasingly engaging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 34 publications
(41 reference statements)
1
31
0
Order By: Relevance
“… Ochalek et al (2020 ) estimated that the CET in China was below one time GDP per capita using a marginal productivity approach. Another study based on the value of the statistical life (VSL) approach found that the CET per QALY in China is close to 1.5 times (ranging from 1.2 to 3.0) of GDP per capita ( Cai et al, 2021 ). Nevertheless, it was still proposed that a higher threshold should be afforded for serious diseases with a high mortality risk ( Cai et al, 2021 ; Lakdawalla and Phelps, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Ochalek et al (2020 ) estimated that the CET in China was below one time GDP per capita using a marginal productivity approach. Another study based on the value of the statistical life (VSL) approach found that the CET per QALY in China is close to 1.5 times (ranging from 1.2 to 3.0) of GDP per capita ( Cai et al, 2021 ). Nevertheless, it was still proposed that a higher threshold should be afforded for serious diseases with a high mortality risk ( Cai et al, 2021 ; Lakdawalla and Phelps, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study based on the value of the statistical life (VSL) approach found that the CET per QALY in China is close to 1.5 times (ranging from 1.2 to 3.0) of GDP per capita ( Cai et al, 2021 ). Nevertheless, it was still proposed that a higher threshold should be afforded for serious diseases with a high mortality risk ( Cai et al, 2021 ; Lakdawalla and Phelps, 2021 ). Three times of GDP per capita is the widely used criterion to judge cost-effectiveness by scholars and policymakers in China, especially in the field of cancer treatment ( Liu et al, 2019 ; Liu et al, 2020 ; Gong et al, 2021 ; Shi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a comparison of our results with those of a very comparable study would provide further evidence of the validity of this research. Cai et al [ 15 ] estimated the monetary value of a QALY based on the value of statistical life to be 1.5 times the GDP per capita in China, equivalent to almost RMB 100,000 (USD 14,952). Song and Lee [ 29 ] found that the average WTP/Q in South Korea was about RMB 145,000 (USD 21,642).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this threshold could only be used to a limited extent for economic evaluations. Using the published literature, Cai et al [ 15 ] first estimated the value of statistical life and then calculated the cost-effective threshold to be 1.5 times the GDP per capita. Furthermore, Zhao et al [ 16 ] proved the feasibility of quantifying the monetary value per QALY with a WTP approach.…”
Section: Introductionmentioning
confidence: 99%
“…In health economics, health effectiveness can be measured by quality-adjusted life years (QALYs). QALY is defined as "a unit of life expectancy that is adjusted for the quality of life during those years" [12], and it serves as the basis for assessing the value of life [13]. An increase in QALYs translates into better health outcomes.…”
Section: How To Co-exist With Covid-19?mentioning
confidence: 99%